APPLICATION OF DIGITAL-BASED MEDIA QUIZZZ TO STUDENT LEARNING OUTCOMES IN PANDEMI TIME - Eli Hermawati; Arrofa Acesta; Gina Noprianti (Kopertis Region IV Jabar and Banten, 2023)
The problem in this study is the use of learning media that is less varied which has an impact on decreasing the learning outcomes of fifth grade students of SD Negeri Maleber. This study aims to determine and describe differences in learning outcomes and differences in learning outcomes improvement between students who apply digital-based quizizz media in the experimental class and students who apply image media to the control class in class V SD Negeri Maleber. This study uses a quasi-experimental method with a non-equivalent control group design. The dependent variable in this study is media quizzz, while the independent variable is learning outcomes. The subjects of this study were students of class VA as the experimental class and students of class VB as the control class. The results of this study indicate that there are differences in learning outcomes and differences in improving learning outcomes between students who apply digital-based quizizz media in the experimental class and students who apply image media to the control class in class V of SD Negeri Maleber